RECURSOS TECNOLÓGICOS Y SU IMPACTO EN EL DESARROLLO ACADÉMICO DE LOS ESTUDIANTES DE 8VO AÑO DE EDUCACION GENERAL BASICA DE LA UNIDAD EDUCATIVA PDTE. VICENTE RAMON ROCA, PERIODO 2024-2025 - MENDOZA MANTUANO STALIN JAVIER (2024)
The use of technological resources in education has proven to be a determining factor in the academic development of students. This case study focuses on analyzing the impact of these resources on the academic performance of students in the 8th year of Basic General Education of the Pdte. Vicente Ramón Roca during the period 2024-2025. The main objective is to determine the impact of technological resources and how these technological tools, such as computers, tablets, educational software and internet access, influence students' learning and school performance. The methodology used includes surveys, interviews, and analysis of academic data. The results obtained confirm that students who use technological resources on a regular basis show a significant improvement in areas such as better management of technology, homework performance and class participation. In addition, an increase in motivation and interest in learning is observed, as this arouses curiosity in learning new things. However, challenges such as lack of access to technology and the need for training for both students and teachers are also identified. The current paradigm has made changes in society in various areas and among them education, it is natural that education adapts to new demands that happen in the world, that is why this era is known as the knowledge society due to the massification of the internet, since it became a point in which education has to address for the standards that are currently needed, The reason for this is because of the impact and freedoms they provide to teachers when teaching and promoting academic development in students. For this reason, technology has become a very important reference for the development of classes and planning activities. Also, we can note that the vital importance that technology had in relation to the time of the covid-19 pandemic worldwide, showed that current education is necessary to take into account the use of technological resources for the development of teaching-learning practice in order to develop students with skills, competencies and knowledge.